Multitasking medialny - Kuźmicka, Kamala (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Media multitasking, defined as audience behaviour when a person is using two or more media sources simultaneously, is a new phenomenon. Now, only 19% of young people are not multitasking. The way information from multiple media streams is processed is different from the normal information processing means. User’s attention is divided between tasks which makes processing of information shallow. The extent of users exposure to each media source creates problems for media research and advertisers as assessing of the exposure level of is very complicated. However, there has been very little research conducted to give a better understanding users’ interaction with each media source. Further research will identify the benefits of multitasking and allow advertisers to target users effectively.